BREAKING OF A NEW DAY IN JOB 38:12-15 - Pinker, Aron (Old Testament Essays, 2018)
Abstract: Exegetes usually approach vv. 12-15 from two different perspectives: cosmological and terrestrial. Some believe that the strophe alludes to astronomical bodies, which are visible in the morning and fade as the light brightens. Most view the strophe as describing the breaking of a new day, and the effect that the growing illumination has on the visibility of Earth’s features and the activity of the wicked upon it. In this approach wickedness is unrealistically perpetrated mainly at night and the day is implicitly described as being an idyllic time. Worse, it presents God as being ineffectual in his treatment of wickedness, since it has to be repeated every morning. Such an admission would hardly fit the majestic God’s speeches. This study proposes a new approach to vv. 12-15, which capitalizes on the possibility that the figure presented in these verses is that of an at dawn wake-up of a military encampment for an imminent battle. The military context presents God as the commander of the universe and makes the fundamental question in the strophe meaningful to Job, who as a chieftain probably had to lead his men to battle. The two basic elements in our strophe are “knowledge” and “advantageous utilization.” God is effective because he can combine these two elements. Man can never be as effective as God, because his “knowledge” will